Radio‐guided and clip‐guided preoperative localization for malignant microcalcifications offer similar performances in breast‐conserving surgery. Issue 5 (11th June 2019) - Corsi, Fabio; Bossi, Daniela; Sartani, Alessandra; Papadopoulou, Ourania; Amadori, Rosella; Scoccia, Elisabetta; Trifirò, Giuseppe; Albasini, Sara; Truffi, Marta; Bonizzi, Arianna; Sorrentino, Luca
Abstract: Obtaining a tailored breast resection is challenging in microcalcifications detected on screening mammography, and an accurate localization is required. The aim of this study was to compare the efficacy of radio‐guided localization (ROLL) versus ultrasound localization of a titanium clip with collagen (TCC) in terms of clear margins, re‐intervention rates, excess of resected breast tissue, and operative times in pure malignant microcalcifications detected on screening mammography. Two hundred and twenty‐one consecutive patients with malignant microcalcifications detected on screening mammography from a tertiary breast unit were reviewed: 177 patients were localized by TCC and 44 patients by stereotactic ROLL. A propensity score‐matched analysis was performed, followed by a logistic regression model, to avoid selection bias. Adequacy of resection was expressed as the calculated resection ratio considering lesion size. No differences were found in clear margins with ROLL versus TCC (77.3% vs 81.8%, adjusted OR 2, P = 0.27). Re‐operation rates were similar, being 11.3% with ROLL and 7.4% with TCC ( P = 0.627). Mean resection volume was 46.2 cm 3 with ROLL versus 54.2 cm 3 with TCC ( P = 0.222). Adjusted mean calculated resection ratio was 1.8 with ROLL and 2.1 with TCC ( P = 0.38). Surgery time was longer with TCC compared to ROLL (69.6 vs 52.7 minutes, P < 0.0001). ROLL and TCC are equally effective to excise malignant microcalcifications with clear margins, providing similar re‐intervention rates and resection volumes.